2016
DOI: 10.1016/j.msec.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonthermal plasma treatment on surface chemistry of commercially-pure titanium and shear bond strength to autopolymerizing acrylic resin

Abstract: The effect of nonthermal plasma on the surface characteristics of commercially pure titanium (cp-Ti), and on the shear bond strength between an autopolymerizing acrylic resin and cp-Ti was investigated. A total of 96 discs of cp-Ti were distributed into four groups (n=24): Po (no surface treatment), SB (sandblasting), Po+NTP and SB+NTP (methane plasma). Surface characterization was performed through surface energy, surface roughness, scanning microscopy, energy dispersive spectroscopy, and X-ray diffraction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
(75 reference statements)
2
15
0
Order By: Relevance
“…These factors directly affect SBS between the ceramic substrates. In addition, the dilution of the Y-TZP with the film constitutents induces strong chemical bonds, providing a film with extra chemically reactive regions without causing damage to the Y-TZP structure [2,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors directly affect SBS between the ceramic substrates. In addition, the dilution of the Y-TZP with the film constitutents induces strong chemical bonds, providing a film with extra chemically reactive regions without causing damage to the Y-TZP structure [2,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…With the use of the hexamethyldisiloxane (HMDSO) monomer and gases such as argon (Ar) and methane (CH 4 ), it is possible to produce a film capable of improving the surface properties of zirconia [23,25,26], transforming its inert surface into a chemically active surface, without any structural damage to the surface [2,25,27]. This film is deposited on the zirconia surface by the PECVD treatment, affecting the hydrophilicity and wettability of the surface, and producing chemically active regions for bonding with other molecules [2,21,23,[25][26][27]. Despite these effects on the ceramic systems, there is no study that evaluated the combination of HMDSO, Ar and CH 4 to improve the SBS between Y-TZP and a nano-fluorapatite glass ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…Three Y-TZP discs from each group were subjected to surface energy analysis with a goniometer (Ramé-Hart 100-00; Ramé-Hart Instrument Co.) using the sessile drop technique. The Owens-Wendt-Rabel-Kaelble method was used to calculate the surface energy by measuring the contact angle between drops of two liquids with different polarities and the Y-TZP disc [8,9,18,20]. Surface roughness analysis was performed with a profilometer (Dektak D150; Veeco).…”
Section: Surface Energy and Roughnessmentioning
confidence: 99%
“…In addition, nonthermal plasma (NTP) treatments have been considered an alternative solution for clinical problems related to adhesion [17,18,19]. In summary, the plasma technique may improve the adhesion by creating new reactive sites onto a substrate surface, which chemically bond to another substrate [17][18][19][20]. A previous study demonstrated that thin films created by methane (CH 4 ) plasma indeed reduce the contact angle and increase free surface energy of some materials used in biomedical devices [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma-deposited thin films are used to produce coatings on different substrates, that can function as a barrier and protect substrates, such as polyamide [20], metals [21] and ceramics [22], from degradation or corrosion, by two well-known techniques plasma-enhanced chemical vapor deposition [20,23,24] and Plasma Immersion Ion Implantation and Deposition [25]. In dentistry, studies showed the use of plasma techniques to immobilize bioactive molecules on the surfaces of bioinert materials [26], for enhancing adhesive qualities in autopolymerized acrylic resin and lithium disilicate ceramic [27,28] and to modify surfaces like titanium and increase protein-adsorption [26], along with others. Within several possible monomers that can be used as a precursor for plasma techniques and the development of thin films, hexamethyldisiloxane (HMDSO), a organosilicon monomer, shows unique potential for this application [29].…”
Section: Introductionmentioning
confidence: 99%